Length–weight relationships of six species of the genera Cobitis and Sabanejewia (Cobitidae) in Iranian river systems. (26th July 2016) - Mousavi‐Sabet, H.; Heidari, A.; Abbasi, K.; Vatandoust, S.
Summary: Length‐weight relationships (LWRs) were estimated for six spined loach species from Iran. Data were collected between 2010 and 2015. These represent the first reports of length–weight data for five of the species ( Cobitis avicennae, Cobitis faridpaki, Cobitis keyvani, Sabanejewia aurata and Sabanejewia caspia ) while also providing additional data on the remaining species ( Cobitis linea ). Five of these species are endemic and the remaining S. caspia, is native to the country. Estimated b values obtained for the studied species ranged from 2.381 for S. aurata to 3.411 for C. keyvani .